2008
DOI: 10.1080/87565640801982320
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Abilities as Precursors of the Early Acquisition of Mathematical Skills During First Through Second Grades

Abstract: The present longitudinal study was designed to investigate precursors of mathematics achievement in children. A total of 72 children were tested at both the beginning and end of first and second grades on measures of the following cognitive abilities: phonology, counting skills, short-term memory, working memory, and verbal and performance IQ. Path analysis models revealed differences in the variables predicting mathematics skills of first and second graders. Specifically, in first graders both short-term and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 47 publications
7
102
2
5
Order By: Relevance
“…The importance of WM also relies on this construct's good predictive value. Indeed, several studies revealed that WM can be considered a strong predictor of mathematics performance in simple arithmetic (Caviola, Mammarella, Lucangeli, & Cornoldi, 2014;Fuchs et al, 2010), and in arithmetical and geometrical problem solving (Giofrè, Mammarella, Ronconi, & Cornoldi, 2013;Passolunghi, Mammarella, & Altoè, 2008). In addition, WM impairments have been demonstrated in participants with DD (Krajewksi, & Schneider, 2009;Mammarella, Caviola, Lucangeli, & Cornoldi, 2013;Passolunghi & Siegel, 2001;Schuchardt, Maehler, & Hasselhorn, 2008).…”
Section: Running Head: Separating Math From Anxietymentioning
confidence: 99%
“…The importance of WM also relies on this construct's good predictive value. Indeed, several studies revealed that WM can be considered a strong predictor of mathematics performance in simple arithmetic (Caviola, Mammarella, Lucangeli, & Cornoldi, 2014;Fuchs et al, 2010), and in arithmetical and geometrical problem solving (Giofrè, Mammarella, Ronconi, & Cornoldi, 2013;Passolunghi, Mammarella, & Altoè, 2008). In addition, WM impairments have been demonstrated in participants with DD (Krajewksi, & Schneider, 2009;Mammarella, Caviola, Lucangeli, & Cornoldi, 2013;Passolunghi & Siegel, 2001;Schuchardt, Maehler, & Hasselhorn, 2008).…”
Section: Running Head: Separating Math From Anxietymentioning
confidence: 99%
“…Perhaps the inclusion of the speed factor was responsible for the better classification results obtained compared to our ROC-analyses. In addition, several authors stressed the importance of executive functions (e.g., Mazzocco & Kover, 2007;Van der Sluis, de Jong, & van der Leij, 2007), working memory (e.g., Bull, Espy, & Wiebe, 2008;Geary & Widaman, 1992;Passolunghi, Mammarella, & Altoe, 2008;Passolunghi & Siegel, 2004;Ricken & Fritz, 2006) and attention (Marzocchi, Lucangeli, De Meo, Fini, & Cornoldi, 2002) in the development of arithmetic (dis)abilities. It even might be so that working memory is related to some of the indicators proposed in the study as well.…”
Section: < Insertmentioning
confidence: 99%
“…A large body of research has shown that WM predicts success in school-related tasks, such as reading comprehension (Carretti, Borella, Cornoldi, & De Beni, 2009), approximate mental addition (Caviola, Mammarella, Cornoldi, & Lucangeli, 2012), mathematical skills (Alloway & Passolunghi, 2011), multi-digit operations (Heathcote, 1994), nonverbal problem-solving (Rasmussen & Bisanz, 2005), mathematical achievement (Bull, Espy, & Wiebe, 2008;Jarvis & Gathercole, 2003;Maybery & Do, 2003;Passolunghi, Mammarella, & Altoè, 2008). Giofrè, Mammarella, Ronconi, and coauthors (2013) recently showed that WM may also be related to geometrical achievement in late adolescence.…”
Section: Cognitive Processes Involved In Geometry: Working Memory Andmentioning
confidence: 99%